Decorative Flame Behavior Study in Visualizing Wavelengths and Frequency: Ruben's Tube Construction Experiment - Ahmad T. Jameel; Mohammed R. Al-Qasaab; Jameel Al-Naffakh (Three E Science Institute, 2021)
Sound waves are very frequent in everyday life, although they are never seen. The particles of the average vibrations are parallel to the direction of propagation of the wave. In this article, the effect of changing the frequency of the sound wave on standing waves was investigated with different hertz frequencies to show technical images that can be visually translated to give fundamental predictions about the origin of the musical combinations, as it was proved that the sound is a pressure wave by giving the vibrations one side while the gas is released the other side. To obtain accurate results, the variables were fixed in the experiment as the type of gas supplied for the same experiments. It is also installed so that the distance between the diaphragm and the amplifier does not differ. The results analyzed after numerous data collection and calculations verify that the generated wavelength and frequency are directly proportional. As the frequency specified in Hz increased, the number of inverse nodes and nodes also increased. Obtaining standing waves helps to understand the nature of sound as a pressure wave, and to give all the details about the experiment and evaluate it. Sources of error and possible solutions to overcome these problems are also mentioned.